White matter and sustained attention in children with attention/deficit-hyperactivity disorder: A longitudinal fixel-based analysis. (December 2022) - Thomson, Phoebe; Vijayakumar, Nandita; Fuelscher, Ian; Malpas, Charles B.; Hazell, Philip; Silk, Timothy J.
Abstract: Sustained attention is a cognitive function with known links to academic success and mental health disorders such as attention/deficit-hyperactivity disorder (ADHD). Several functional networks are critical to sustained attention, however the association between white matter maturation in tracts linking functional nodes and sustained attention in typical and atypical development is unknown. 309 diffusion-weighted imaging scans were acquired from 161 children and adolescents (80 ADHD, 81 control) at up to three timepoints over ages 9–14. A fixel-based analysis approach was used to calculate mean fiber density and fiber-bundle cross section in tracts of interest. Sustained attention was measured using omission errors and response time variability on the out-of-scanner sustained attention to response task. Linear mixed effects models examined associations of age, group and white matter metrics with sustained attention. Greater fiber density in the bilateral superior longitudinal fasciculus (SLF) I and right SLF II was associated with fewer attention errors in the control group only. In ADHD and control groups, greater fiber density in the left ILF and right thalamo-premotor pathway, as well as greater fiber cross-section in the left SLF I and II and right SLF III, was associated with better sustained attention. Relationships were consistent across the age span. Results suggest that greater axon diameter or number in the dorsal and middle SLF may facilitate sustained attention in neurotypical children but does not assist those with ADHD potentially due to disorder-related alterations in this region. Greater capacity for information transfer across the SLF was associated with attention maintenance in 9–14-year-olds regardless of diagnostic status, suggesting white matter macrostructure may also be important for attention maintenance. White matter and sustained attention associations were consistent across the longitudinal study, according with the stability of structural organization over this time. Future studies can investigate modifiability of white matter properties through ADHD medications.